What occupational preference types dominate among nurses and paramedics with implications for wellbeing?: A scoping review. (20th March 2020) - Mason, Rod; Roodenburg, John; Williams, Brett
Abstract: Understanding the occupational typological nature of nursing and paramedicine and the typological preferences of these within the professions offers significant evidence of factors that can facilitate wellbeing and efficiencies. Arksey and O'Malley's five‐stage scoping methodology was used to review the literature. The research question used to guide this scoping review was: Which Holland code is more dominant among nurses and paramedics? Nine articles were included in this review, from which two broad themes emerged: Job satisfaction/academic success; and personality‐employment fit across gender and subgroups within the same occupation. While the Social (S) personality type dominated across the studies for both nurses and paramedics, overall, the studies identified various combinations of the personality profile and, in some cases, personality types foreign to the occupation also formed part of the Holland code. Congruence can be thought of as playing an important role in nurses'/paramedics' overall well‐being regardless of the order of their three dominant personality types.